Probabilistic Seismic Hazard Assessment Using Gumbel’s Extreme Value Distribution in the Himalayan Arc (71.6°E – 97°E and 37.5°N – 26.6°N) - Subedi, Anil; Parajuli, Dilip; Thapa, Manoj; Sigdel, Dinesh; Bogati, Shankar; Subedi, Tilak; Tiwari, Ram Krishna; Paudyal , Harihar (BMC Journal of Scientific Research, 2025)
The Himalayan arc, formed by the ongoing collision of the Indian and Eurasian plates, ranks among the most seismically active zones worldwide. For this study, a probabilistic seismic hazard assessment was carried out using Gumbel’s Extreme Value Distribution (Type-I) applied to a declustered earthquake catalog spanning 1900 to 1 April 2025. To reflect tectonic variability across the region (71.6°E 97°E; 26.6°N–37.5°N), the arc was subdivided into five segments: Far Western, Western, Central-I, Central-II, and Eastern Himalaya.The study makes it clear that the risk of earthquakes goes down from west to east across the Himalayan arc. In the western parts of the Western Himalaya, big earthquakes tend to happen very rarely, with a Mw 7.5 earthquake happening every 9,300 years. The central region, on the other hand, has much shorter intervals. The Central-II Himalaya is especially at risk because Mw 7.5 events happen about every 127 years and Mw 8.0 events happen about every 407 years. That means there is more than a 55% chance that an Mw ≥ 7.5 earthquake will happen in the next 100 years. It is interesting that the eastern Himalaya is more likely to have earthquakes than the western parts. These results highlight the arc’s crucial spatial heterogeneity in seismic risk. In addition, the information contained in these results is so large there are many indicators for better preparing for catastrophes and a greater sense of the importance of developing strong infrastructure and construction guidelines. Two regions that require the most attention to strong infrastructure and building guidelines are Central-II and Eastern Himalayas due to their fragile conditions. If there are even minor changes to current planning and building regulations, then the impact of these changes on future events will be immense.